2021
DOI: 10.1007/s12649-021-01471-5
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Nitrogen-Enriched Chars as Circular Fertilizers

Abstract: Purpose Charred materials are low in bioavailable nitrogen (N) due to gaseous losses and the formation of recalcitrant structures during pyrolysis. Enriching chars with N from wastewaters offers a possibility to upgrade the agronomic value of the chars and manage the liquids. For assessing the practical feasibility of the approach, more information on the extent of the retention and release of the loaded N is needed. Methods The ammonium-N (NH4-N) retentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The total N present in the developed lignorea was 30–35%, estimated through KELPLUS instrument. Similarly, ref estimated total N in chars before and after loading N using the Kjeldahl method. Ref reported the nitrogen content was higher in nanozeourea (28%N) compared to zeourea.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The total N present in the developed lignorea was 30–35%, estimated through KELPLUS instrument. Similarly, ref estimated total N in chars before and after loading N using the Kjeldahl method. Ref reported the nitrogen content was higher in nanozeourea (28%N) compared to zeourea.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The N enrichment may be the result of N sorption or microbial N retention on the biochar surface, but this was not su cient to affect the C:N ratio of the growing medium blend with biochar nor the other N related characteristics. In general, the N sorption capacity of biochars and the amounts of N retained within biochars in bioavailable form are small (Keskinen et al 2021;Rasse et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Increase in NUE with BCF has largely been attributed to a putative slow-release effect that biochar matrices have on N fertilizers (Cai et al 2016;Dong et al 2019;Ibrahim et al 2020;Manikandan and Subramanian 2013). However, when mineral N was loaded on wood and sludge biochar surfaces, Keskinen et al (2021) reported no observable slow release effect. This finding is not surprising given that sorption and desorption of N on biochar surfaces is a rapid process often occurring on timescales of less than a day (Kizito et al 2015;Wang et al 2020).…”
Section: The Theory Of N-efficient Bcfsmentioning
confidence: 99%